2018
DOI: 10.1128/jb.00342-18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Biochemical, and Molecular Characterization of Methanosarcina barkeri Mutants Lacking Three Distinct Classes of Hydrogenase

Abstract: The methanogenic archaeon encodes three distinct types of hydrogenase, whose functions vary depending on the growth substrate. These include the F-dependent (Frh), methanophenazine-dependent (Vht), and ferredoxin-dependent (Ech) hydrogenases. To investigate their physiological roles, we characterized a series of mutants lacking each hydrogenase in various combinations. Mutants lacking Frh, Vht, or Ech in any combination failed to grow on H-CO, whereas only Vht and Ech were essential for growth on acetate. In c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…On the other hand, in reactors inoculated with M. barkeri , the detected H 2 stabilized at 0.065 ± 0.02 mM, similar to concentrations observed for co-cultures of M. barkeri with (0.077 ± 0.03 mM) or without conductive particles (0.076 ± 0.06 mM) and in pure culture (0.068 mM). This is supported by previous research, which demonstrated H 2 -cycling (H 2 -production and H 2 -uptake) in M. barkeri (Kulkarni et al, 2009, 2018; Mand et al, 2018). The cellular evolved H 2 is well above the H 2 -uptake threshold for M. barkeri (296 nM −376 nM) (Kral et al, 1998; Lovley, 1985) possibly because in these cultures there is an alternative, competitive electron donor.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, in reactors inoculated with M. barkeri , the detected H 2 stabilized at 0.065 ± 0.02 mM, similar to concentrations observed for co-cultures of M. barkeri with (0.077 ± 0.03 mM) or without conductive particles (0.076 ± 0.06 mM) and in pure culture (0.068 mM). This is supported by previous research, which demonstrated H 2 -cycling (H 2 -production and H 2 -uptake) in M. barkeri (Kulkarni et al, 2009, 2018; Mand et al, 2018). The cellular evolved H 2 is well above the H 2 -uptake threshold for M. barkeri (296 nM −376 nM) (Kral et al, 1998; Lovley, 1985) possibly because in these cultures there is an alternative, competitive electron donor.…”
Section: Resultssupporting
confidence: 90%
“…Bacterial Culturing Conditions. The strains of Methanosarcina barkeri used have 325 been described previously (24,27). In brief, a background strain containing the Δhpt::ΦC31int-attP promoter fusion was utilized for wild-type experiments as this strain was utilized for genetic manipulations (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, a background strain containing the Δhpt::ΦC31int-attP promoter fusion was utilized for wild-type experiments as this strain was utilized for genetic manipulations (28,29). A hydrogenase deletion mutant with the Ech, Vhu, and Fhr hydrogenases removed was utilized for delta-hydrogenase experiments (24). Each strain was provided by William Metcalf at the University of 330 Illinois at Urbana-Champaign.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations